The concept of tolerance in Islam and mysticism - Tursunovna, Sharipova Oygul (Indonesian Journal of Innovation Studies, 2019)
This article analyzes the issues of tolerance in Islamic teachings and the Sufi doctrine, which is an important part of it. It also outlines the religious-philosophical and educational aspects of the concept of tolerance. The results will be mentioned for the further discussions.